2001
DOI: 10.1159/000047616
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Experimental Ischemia in Cats for Stroke Management: A Comparative Reevaluation

Abstract: Repeat studies in animal models of acute focal ischemia can be compared to incidental studies in the course of ischemic stroke in order to shed light on the development of changes causing ischemic infarcts or recovery of critically perfused tissue. Positron emission tomography (PET) studies of regional cerebral blood flow, cerebral metabolic rate for oxygen, oxygen extraction fraction (OEF), cerebral metabolic rate of glucose and flumazenil (FMZ) binding in the cat middle cerebral artery occlusion (MCAO) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…We investigated thoracic and middle cerebral arteries. Relaxation of cerebral vessels during and after an ischemia/reperfusion leads to collateral cerebral blood flow, and thus characterizes an intrinsic strategy of the cerebral vasculature to protect neuroglial structures but also vasculature including endothelium against ischemic injury (Heiss et al, 2001), likewise reported for the heart (Koerselman et al, 2003; Meier et al, 2013). Indeed, cerebral collateral status and sufficiently enlarged calibers of collateral arteries have recently been identified as most relevant for final infarct volume, vasogenic edema formation (with subsequent midline shift), and hence patient outcome (Volny et al, 2016; van den Wijngaard et al, 2016; van der Hoeven et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…We investigated thoracic and middle cerebral arteries. Relaxation of cerebral vessels during and after an ischemia/reperfusion leads to collateral cerebral blood flow, and thus characterizes an intrinsic strategy of the cerebral vasculature to protect neuroglial structures but also vasculature including endothelium against ischemic injury (Heiss et al, 2001), likewise reported for the heart (Koerselman et al, 2003; Meier et al, 2013). Indeed, cerebral collateral status and sufficiently enlarged calibers of collateral arteries have recently been identified as most relevant for final infarct volume, vasogenic edema formation (with subsequent midline shift), and hence patient outcome (Volny et al, 2016; van den Wijngaard et al, 2016; van der Hoeven et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Rabbits have an arterial anatomy that permits endovascular autologous clot occlusion of various intracranial arteries including the MCA [22] and the basilar artery [23], however their brains are lissencephalic like the rat and not generally representative of the human gyrencephalic brain. Cats are of a similar size to rabbits and have a gyrencephalic brain, however their vascular anatomy precludes an endovascular approach to occlusion and the surgical approach is transorbital [24]. Both rabbits and cats are considerably smaller than sheep or pigs, and although weight itself does not predict phylogenetic order, larger brains allow for easier surgical manipulation and limit the requirement of higher resolution imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This tissue, termed the penumbra, 1 is perfused at a level within the thresholds of functional impairment and morphological integrity and has the capacity to recover if perfusion is improved. The extent of this tissue compartment is dependent on residual flow and duration of flow disturbance: It can be clearly demonstrated in animal experiments with permanent and transient occlusion of cerebral vessels 11 that the volume of functionally impaired but morphologically intact tissue is large and involves even the centre of the vascular territory with impaired blood supply immediately after the onset of the perfusional disturbance, and it becomes progressively smaller with time elapsed since the vascular attack. 5 This concept as developed in animal experiments defines the penumbra as a dynamic process depending on residual perfusion and duration, with conversion into irreversible neuronal damage over time, progressing from the centre of dense ischemia to the surrounding tissue with less severe but still critically hypoperfused adjacent areas.…”
Section: Detection Of Penumbramentioning
confidence: 99%